2022
DOI: 10.1093/molehr/gaac011
|View full text |Cite
|
Sign up to set email alerts
|

On the origins and fate of chromosomal abnormalities in human preimplantation embryos: an unsolved riddle

Abstract: About 8 out of 10 human embryos obtained in vitro harbour chromosomal abnormalities of either meiotic or mitotic origin. Abnormalities of mitotic origin lead to chromosomal mosaicism, a phenomenon which has sparked much debate lately as it confounds results obtained through preimplantation genetic testing for aneuploidy (PGT-A). PGT-A in itself is still highly debated, not only on the modalities of its execution, but also on whether it should be offered to patients at all. We will focus on post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 135 publications
2
13
0
Order By: Relevance
“…Since then, with the introduction of comprehensive chromosome testing methods, numerous studies have confirmed this association (Fragouli et al , 2013; Capalbo et al , 2014; Qi et al , 2014; Maurer et al , 2015). However, all of these studies were limited by the use of earlier methodologies that did not discriminate between full and intermediate copy number changes for all chromosomes, limited sampling of embryo cells, or analysis of selected clinical-grade embryos only (reviewed by Regin et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, with the introduction of comprehensive chromosome testing methods, numerous studies have confirmed this association (Fragouli et al , 2013; Capalbo et al , 2014; Qi et al , 2014; Maurer et al , 2015). However, all of these studies were limited by the use of earlier methodologies that did not discriminate between full and intermediate copy number changes for all chromosomes, limited sampling of embryo cells, or analysis of selected clinical-grade embryos only (reviewed by Regin et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms behind this selective clearance are thought to be mediated by two well-studied intracellular stress responses 10 . First, aneuploidy results in gene-dosage defects, leading to an unbalanced protein pool and proteotoxic stress.…”
Section: Introductionmentioning
confidence: 99%
“…If this remains unresolved by activation of autophagy, CASP8/LC3B/p62 will interact to activate the apoptosis cascade (Pan et al, 2011;Stingele et al, 2012;Dürrbaum et al, 2014). Second, aneuploidy results in replication stress that can lead to DNA-damage, resulting in p53 activation and ultimately to apoptosis (Zhu et al, 2018;Regin et al, 2022). Bolton et al (Bolton et al, 2016) showed that aneuploid cells are selectively cleared from chimeric mouse embryos generated from control blastomeres mixed with aneuploid blastomeres obtained using a treatment with the SAC inhibitor reversine.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations